PESAN DAKWAH SUNAN DRAJAT DALAM WEJANGAN CATUR PIWULANG: Analisis Semiotika Charles Sanders Pierce - Ainur Rofiq; Abdur Rozaq (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
Islam is a religion that calls on its followers to carry out da'wah through various methods, one of which is Sunan Drajat who preaches through the teachings of Catur Piwulang (four teachings). This discourse contains many preaching messages if examined further. Therefore, researchers want to know more deeply about the preaching contained in it by analyzing the preaching. This research aims to: Find out the results of the analysis of Catur Piwulang's discourse using Charles Sanders Pierce's Semiotic Theory, as well as to find out the da'wah message contained. This research uses descriptive qualitative research. The researcher uses Charles Sanders Pierce's semiotic analysis research approach to dissect the discourse of